Adapting sales and operations planning to dynamic and complex supply chains - Christian Kalla; Luiz Felipe Scavarda; Rodrigo Goyannes Gusm\~ao Caiado; Bernd Hellingrath (Review of Managerial Science, 2025)
Traditional supply chain planning (SCP) processes are generally effective in stable business environments where demand and supply are predictable and reliable. However, firms are no longer operating within static systems. Instead, they are embedded in dynamic and complex supply chains that challenge the effectiveness of traditional SCP processes, necessitating their adaptation. In this context, this paper focuses on sales and operations planning (S&OP), representing an SCP process on a tactical level. The paper introduces a novel framework for adapting the S&OP process to dynamic and complex supply chains. An empirical research approach is employed to achieve this goal, embracing a multiple case study of three firms operating in different contexts. The research leverages Complex Adaptive Systems (CAS) theory as a theoretical lens to embrace the characteristics of dynamic and complex supply chains of the three firms, representing the first application of this theory within the domain of S&OP research. The proposed framework encompasses five propositions designed to advance the theoretical understanding of S&OP, thereby contributing to the development of a unified S&OP theory. Moreover, the framework provides practical guidance for managers seeking to adapt their firm's S&OP process towards dynamic and complex supply chains.
Additional information: M1;D20;L2
Keywords: 330; Supply chain planning; Tactical planning; S&OP; Risk management; Complex adaptive systems; Sales and operations execution